New Zealand : 2011 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for New Zealand. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
New Zealand's recovery has stalled since mid-2010. Spare capacity has helped contain inflation. The Reserve Bank of New Zealand (RBNZ) lifted its policy rate in two steps from a record low of 2.5 percent to 3 percent in mid-2010. The exchange rate appreciated and financial markets have largely recovered from the global financial crisis. The banking sector remains profitable and is dominated by four subsidiaries of Australian banks that performed well during the crisis. The 2010 Canterbury earthquakes have disrupted economic activity, reduced wealth, and weakened confidence.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet